A proposed norms' benefits awareness framework for norms adoption - Itaiwi, A.-M.K. (2017)
Several works have been conducted on norms detection and identification, but almost none has been found to explore the concept of norm's benefit awareness that triggers agents' belief to adopt new norms. The literature discuss norms' adoption by agents which are not aware of the benefits of the adopted norms, but use some mining algorithms to identify the norms from a set of observed events. In this paper, we propose a novel solution to this problem that calculates the benefit of a norm to its utility and subsequently decides to adopt or reject the norm. © 2014 IEEE.